How tax progression affects effort and employment - Erkki Koskela; Ronnie Schöb (Institute for the Study of Labor (IZA), 2007)
Within an efficiency wage framework, we study the effects of two revenue-neutral tax reforms that change the progressivity of the labour tax system. A revenue-neutral increase in both the wage tax and tax exemption and a revenue-neutral change in the composition of labour taxation towards the tax with the smaller tax base will lead to the same results: they moderate wages, workers' effort, effective labour input and aggregate output. Whether employment rises or falls, however, depends in both reforms on the magnitude of the pre-reform total tax wedge. The larger this tax wedge is, the more negative is the impact of reforms on workers' effort. A larger total tax wedge increases the negative effect of tax progression on labour productivity and thus thwarts the positive employment effect of wage moderation.
Keywords: 330; Lohnsteuer; Steuerreform; Steuerprogression; Steuerwirkung; Arbeitsproduktivität; Beschäftigungseffekt; Theorie